Penyuluhan Fisioterapi Komunitas dalam Peningkatan Pengetahuan Tentang Sprain Ankle pada Siswa-Siswi Kelas VII MTS Almaarif 01 Singosari - Arlita Tri Wahyuniningsih; Rakhmad Rosadi; Ratna Vidya Amelia (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
An ankle sprain is an injury experienced by school-age adolescents due to a lack of caution during activities, as well as high physical activity in sports activities, such as playing soccer, running, and other sports. Signs and symptoms of an ankle sprain are pain and edema. Interventions for ankle sprains can be categorized into functional rehabilitation and initial management by performing the RICE (Rest, Ice, Compression, and Elevation) method followed by joint mobilization to increase the scope of joint motion. This counseling aims to increase the knowledge of seventh-grade students of MTS Almaarif 01 Singosari about ankle sprains. Counseling was conducted using an interactive demonstration method using leaflet print media, with 14 male and 18 female students. The results of counseling are found in the pre-test and post-test evaluation of increased knowledge about ankle sprain in class VII students of MTS Almaarif 01 Singosari.